2004
DOI: 10.1149/1.1625592
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of Cathode Activity for Fe-Rich and Cu-Rich Intermetallic Particles via Cathodic Corrosion from Dioxygen Reduction at Aluminum Alloy 2024-T3

Abstract: A wall-jet flow cell was used to study O 2 reduction at AA2024-T3. In buffered O 2 -saturated solution the current density was 2% of the diffusion-limited value and relatively stable with time. In unbuffered solution the current density was 25-50% of the diffusion-limited value. The higher currents under unbuffered conditions are attributed to production of OH Ϫ via O 2 reduction at the intermetallic particles ͑IPs͒ at AA2024-T3. Trenching was observed around both Cu-rich and Fe-rich IPs. This cathodic corrosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 15 publications
(29 reference statements)
2
33
0
Order By: Relevance
“…Again, this lower ORR current on the bare and anodized alloy samples results from the presence of simultaneous cathodic ͑ORR͒ and anodic ͑oxide growth͒ processes, as previously described. 22,35 Zr-ODP treated samples were examined using the same procedure as in Fig. 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Again, this lower ORR current on the bare and anodized alloy samples results from the presence of simultaneous cathodic ͑ORR͒ and anodic ͑oxide growth͒ processes, as previously described. 22,35 Zr-ODP treated samples were examined using the same procedure as in Fig. 1.…”
Section: Resultsmentioning
confidence: 99%
“…The influence of Zr-ODP treatments on the inhibition of O 2 reduction was examined using a solutionexchange protocol as previously described. 22,35 In these experiments, the sample was initially exposed to N 2 -saturated 0.1 M Na 2 SO 4 , where it was held at −0.8 V for 100 s, followed by a rapid exchange ͑at constant potential͒ to O 2 -saturated 0.1 M Na 2 SO 4 solution, where it was held at the same potential for 1000 s. It has previously been shown that in this wall-jet cell at this flow rate, −0.8 V is on the limiting current plateau for the ORR at both pure Cu and pure Fe and is near the apparent half-wave potential for AA2024-T3. 17,22,35 Thus, measurements at this potential are appropriate for detecting changes in the ORR current density caused by the surface coatings.…”
Section: Methodsmentioning
confidence: 99%
“…4c, two regions where trenching or particle removal may have taken place are evident ͑shown in rectangles͒; however, these appear to have been caused by IP removal during the polishing process. 6 Other than these two locations, the treated sample shows no trenching adjacent to particles. Confirmation of the presence of the modifying layer was accomplished by acquiring a broad area AES spectrum as well as multiple-point AES spectra on the alloy surface.…”
Section: C325mentioning
confidence: 94%
“…The wall-jet flow cell used for voltammetry and chronoamperometric experiments was previously described. 6,7 This cell used gravitational flow for the delivery of the supporting electrolyte, giving a smooth, pulseless flow. The rate of delivery to the electrode surface was monitored by a downstream digital flowmeter ͑Agilent Technologies͒, ensuring that flow was kept within the range in which the cell was known to obey theory ͑1.55-1.70 mL min −1 ͒.…”
Section: Methodsmentioning
confidence: 99%
“…Other studies have looked directly at localized corrosion behavior. Cathodic activity of Fe and Cu rich inclusions on surfaces of Al 2024 have been examined [19,20]. SECM has been used to initiate [21] and detect [22] localized corrosion at steel surfaces.…”
Section: Introductionmentioning
confidence: 99%